Identification and characterization of retinoid-active short-chain dehydrogenases/reductases in Drosophila melanogaster - Belyaeva, Olga V.; Lee, Seung-Ah; Kolupaev, Oleg V.; Kedishvili, Natalia Y. (Biochimica et biophysica acta, 2009)
In chordates, retinoid metabolism is an important target of short-chain dehydrogenases/reductases (SDRs). It is not known whether SDRs play a role in retinoid metabolism of protostomes, such as Drosophila melanogaster. Drosophila genome was searched for genes encoding proteins with ∼ 50% identity to human retinol dehydrogenase 12 (RDH12). The corresponding proteins were expressed in Sf9 cells and biochemically characterized. Their phylogenetic relationships were analyzed using PHYLIP software. A total of six Drosophila SDR genes were identified. Five of these genes are clustered on chromosome 2 and one is located on chromosome X. The deduced proteins are 300 to 406 amino acids long and are associated with microsomal membranes. They recognize all- trans-retinaldehyde and all- trans-3-hydroxyretinaldehyde as substrates and prefer NADPH as a cofactor. Phylogenetically, Drosophila SDRs belong to the same branch of the SDR superfamily as human RDH12, indicating a common ancestry early in bilaterian evolution, before a protostome–deuterostome split. Similarities in the substrate and cofactor specificities of Drosophila versus human SDRs suggest conservation of their function in retinoid metabolism throughout protostome and deuterostome phyla. The discovery of Drosophila retinaldehyde reductases sheds new light on the conversion of β-carotene and zeaxantine to visual pigment and provides a better understanding of the evolutionary roots of retinoid-active SDRs.